Data from: Origins of the Greenland shark (Somniosus microcephalus): impacts of ice-olation and introgression - Walter, Ryan P.; Roy, Denis; Hussey, Nigel E.; Stelbrink, Björn; Kovacs, Kit M.; Lydersen, Christian; McMeans, Bailey C.; Svavarsson, Jörundur; Kessel, Steven T.; Biton Porsmoguer, Sebastian; Wildes, Sharon; Tribuzio, Cindy A.; et al. (Dryad Digital Repository, 2017)
Herein, we use genetic data from 277 sleeper sharks to perform coalescent-based modeling to test the hypothesis of early Quaternary emergence of the Greenland shark (Somniosus microcephalus) from ancestral sleeper sharks in the Canadian Arctic-Subarctic region. Our results show that morphologically cryptic somniosids S. microcephalus and Somniosus pacificus can be genetically distinguished using combined mitochondrial and nuclear DNA markers. Our data confirm the presence of genetically admixed individuals in the Canadian Arctic and sub-Arctic, and temperate Eastern Atlantic regions, suggesting introgressive hybridization upon secondary contact following the initial species divergence. Conservative substitution rates fitted to an Isolation with Migration (IM) model indicate a likely species divergence time of 2.34 Ma, using the mitochondrial sequence DNA, which in conjunction with the geographic distribution of admixtures and Pacific signatures likely indicates speciation associated with processes other than the closing of the Isthmus of Panama. This time span coincides with further planetary cooling in the early Quaternary period followed by the onset of oscillating glacial-interglacial cycles. We propose that the initial S. microcephalus–S. pacificus split, and subsequent hybridization events, were likely associated with the onset of Pleistocene glacial oscillations, whereby fluctuating sea levels constrained connectivity among Arctic oceanic basins, Arctic marginal seas, and the North Atlantic Ocean. Our data demonstrates support for the evolutionary consequences of oscillatory vicariance via transient oceanic isolation with subsequent secondary contact associated with fluctuating sea levels throughout the Quaternary period—which may serve as a model for the origins of Arctic marine fauna on a broad taxonomic scale. 61 haplotypes cytb 702 bases in phylip formatPhylip file listing 61 haplotypes of partial reads of the mtDNA cytochrome b gene used in Walter et al., The first 22 haplotypes originally published ...